Pentingnya Pendidikan Karakter Di Masa Pandemi Covid 19 - Suparwati, Dwi (Universitas Sebelas Maret, 2020)
Character education is very important in order to shape the character of the nation. Character education can make students become social beings who help each other, are civilized and polite. Teaching and learning activities carried out in Indonesia previously were face-to-face or offline learning. At the time of face-to-face or offline learning, teachers can easily observe the character of students and can provide direction and character education easily. However, the COVID-19 pandemic has forced the change of face-to-face or offline learning to be replaced by online or virtual. For this reason, collaboration and communication between teachers and parents of students to jointly apply character education is very necessary. Teachers can provide good habituation tasks, by implementing PPK (Strengthening Character Education) in online or virtual activities, and parents working with teachers to supervise student activities from home.